Peran Sekolah Penggerak dalam Meningkatkan Prestasi Siswa - Wahyuni, Sri (IJOCE: Indonesia Journal of Civic Education, 2026)
This study aims to describe the role of the “Sekolah Penggerak” program in enhancing student achievement at SMP Negeri 22 Bengkulu City. The study employs a qualitative approach using a descriptive method. Data collection techniques included observation, interviews, and documentation. The research subjects consisted of the school principal, teachers, and students at SMP Negeri 22 Bengkulu City. The results indicate that the “Sekolah Penggerak” program plays a significant role in the implementation of the “Kurikulum Merdeka” (Independent Curriculum), particularly in facilitating differentiated instruction, strengthening literacy and numeracy, and fostering student character development. Furthermore, teachers and principals who received training and mentoring were able to manage instruction more effectively and in a student-centered manner. However, challenges remain, such as limited facilities and infrastructure, low technological proficiency among some teachers, and a lack of active student participation. In conclusion, the “Sekolah Penggerak” program at SMP Negeri 22 Bengkulu City has demonstrated a positive role in improving student achievement across cognitive, affective, and psychomotor domains.   Keywords: Driving School, Independent Curriculum, Student Achievement, Competence, Educational Transformation.